The current socioeconomic and regulatory landscape of immune effector cell therapies - Sainatham, Chiranjeevi; Yadav, Devvrat; Dilli Babu, Aravind; Tallapalli, Jayanth Reddy; Kanagala, Sai Gautham; Filippov, Evgenii; Murillo Chavez, Franco; Ahmed, Nausheen; Lutfi, Forat (Frontiers in Medicine, 2024)
Immune cell effector therapies, including chimeric antigen receptor (CAR)-T cells, T-cell receptor (TCR) T cells, natural killer (NK) cells, and macrophage-based therapies, represent a transformative approach to cancer treatment, harnessing the immune system to target and eradicate malignant cells. CAR-T therapy, the most established among these, involves engineering T cells to express CARs specific to cancer cell antigens, showing remarkable efficacy in hematologic malignancies. Similarly, TCR-modified therapies, which reprogram T cells to recognize intracellular tumor antigens presented by major histocompatibility complex (MHC) molecules, offer promise for a range of solid tumors. NK-cell therapies leverage NK cells' innate cytotoxicity, providing an allogeneic approach that avoids some of the immune-related complications associated with T-cell-based therapies. Macrophage-based therapies, still in the early stages of development, focus on reprogramming macrophages to stimulate an immune response against cancer cells in the tumor microenvironment. Despite their promise, socioeconomic and regulatory challenges hinder the accessibility and scalability of immune cell effector therapies. These treatments are costly, with CAR-T therapies currently exceeding $400,000 per patient, creating significant disparities in access based on socioeconomic status and geographic location. The high manufacturing costs stem from the personalized, labor-intensive processes of harvesting, modifying, and expanding patients' cells. Moreover, complex logistics for manufacturing and delivering these therapies limit their reach, particularly in low-resource settings. Regulatory pathways further complicate the landscape. In the United States., the Food and Drug Administration's (FDA) accelerated approval processes for cell-based therapies facilitate innovation but do not address cost-related barriers. In Europe, the European Medicines Agency (EMA) offers adaptive pathways, yet decentralized reimbursement systems create uneven access across member states. Additionally, differing regulatory standards for manufacturing and quality control worldwide pose global harmonization and access hurdles. To expand the reach of immune effector cell therapies, a multipronged approach is needed streamlined regulatory frameworks, policies to reduce treatment costs, and international collaborations to standardize manufacturing. Addressing these socioeconomic and regulatory obstacles is essential to make these life-saving therapies accessible to a broader patient population worldwide. We present a literature review on the current landscape of immune effector cell therapies and barriers to access to currently approved therapies.